Customer service marketing managing the customer experience - Torres, Edwin N.; Zhang, Tingting (Christina) (Routledge, 2023)
"This timely book is a comprehensive overview of customer service principles, theories, and practices. It looks at the best practices of service enterprises and the delivery of superior customer service. It also includes classic and contemporary theories relating to the consumers, managers, and their behaviors in organizational setting. The book uses real life applications through examples from business enterprises in various service sectors including hotels, restaurants, theme parks, event management, airlines, cruises, (e-)retailers, finance. The book covers important concepts in service design and delivery including customer experiences, peer-to-peer services, the organization's servicescape, quality measurement tools, and use of technologies. The book also gives insights into consumers including their expectations, attitudes, emotions, word-of-mouth behaviors, and strategies to ensure their loyalty. It also looks at developments in service theory and practice which remain relatively unexplored by existing textbooks. Filled with real-world case studies in various service sectors, this textbook will be particularly useful for students in hospitality guest services and services marketing"--